Mitral annulus calcification: current management and future challenges. (September 2019) - Carino, Davide; Agostinelli, Andrea; El Qarra, Suad; Gripshi, Florida; Nicolini, Francesco
Mitral annulus calcification is a chronic degenerative process in the fibrous base of the mitral valve. Assessment and treatment of mitral valve disease in patients with severe mitral annulus calcification is challenging, and a multimodal approach is helpful to delineate its severity and anatomic features, and to guide the therapeutic strategy. This article reviews the current literature to provide a clinically relevant description of mitral annulus calcification, analyze the diagnostic pathway of a patient with mitral annulus calcification, and summarize the therapeutic options.